Classificação do desempenho térmico da envoltória de habitação popular em concreto armado - Raquel Diniz Oliveira (2015)
This study aims to analyze the thermal performance in naturally ventilated Social Housing, with concrete walls (U=4.40 W/m²K, = 0.4), in Brazilian territory. The building envelope was evaluated by the main thermal performance Brazilian standards (NBR 15,220/2005, NBR 15,575/2013, RTQ-R/2012 and Blue House Labeling/2014), considering the simplified and computer simulation methods using Energy Plus software. Eight cities represents the Brazilian bioclimatic zones and climate differences. It proposes some changes to unapproved requirements especially in building envelope. Moreover, it adds shutters in the bedrooms and direction changes in the site plan. Results showed that the simplified method was, in general, stricter than the simulation method. It founds contradictions in the simulation method limits set by the NBR 15,575 that allowed the approval uncomfortable dwellings for users. For the RTQ-R it notes that the limit for winter conditions enable, in some cases, hide the inappropriate thermal behavior of the building system in their evaluation. Concluding the concrete walls can be used in Brazil with some building system changes, except in the hottest bioclimatic zones. For these cases, natural ventilation, windows shutters and as well as the envelope insulation increase proved insufficient to ensure human acceptable conditions without use artificial ventilation and air conditioning equipment.